Kinetics of hydrogen desorption from titanium hydride under isothermal conditions. (18th January 2018) - Ma, Mingwang; Wang, Lei; Tang, Binghua; Lyu, Ping; Xiang, Wei; Wang, Yuan; Tan, Xiaohua
Abstract: Thermal desorption behaviours of titanium hydride powders under isothermal heat treatment conditions were studied using simultaneous thermogravimetry and thermal desorption spectroscopy (TG-TDS) method. The crystal structures and chemical compositions of the heat treated samples were investigated by X-ray diffraction analysis (XRD) and X-ray photoelectron spectroscopy (XPS), respectively. It was found that the isothermal heating condition was of importance for the ordering of oxygen or surface oxidation. The phase transformation sequences during long time heating were established by combining the changing trends in the temperature/hydrogen content with the TiH phase diagram. A method for evaluating the kinetic parameters for different phase regions was proposed. The activation energies were calculated for these phase regions, and the corresponding rate-limiting steps were suggested. Highlights: Controversial γ-TiH was observed at room temperature after heat treatment at 400 °C. Oxygen ordering took place under isothermal heating conditions below 500 °C. Phase transformation sequence was determined as δ → β + δ → β → α + β → α. Activation energies of various phase regions were in the range of 102–160 kJ/mol.